VISUAL ANALYSIS OF AI-GENERATED IMAGE DIGITAL PORTRAIT WITH GHIBLI STUDIO STYLE - Rifa Annisa; Aprilia Ariesty Wibowo; Ariesta Beta Nandya (Desain Komunikasi Visual, Manajemen Desain dan Periklanan (Demandia), 2026)
The rapid development of artificial intelligence technology is capable of interpreting and creating visual artwork based on human input through a platform. Although AI offers efficiency in creating works, the similarity to existing visual styles sparks debate about originality and ethics. This issue gained prominence with the emergence of AI generated Studio Ghibli-style digital portraits on social media. The main issue discussed in this study is how AI-generated images differ visually and technically from Studio Ghibli's original works. Previous studies focused on copyright and data privacy, research comparing visual is still limited. This research aims to fill this gap by conducting a visual comparative analysis between AI-generated works and Studio Ghibli's animation style using Feldman's theory. This comparison clearly shows how AI-generated visuals compare to human-made ones based on visual and technical analysis.The findings show that AI can copy surface features well, but it cannot achieve accurate anatomy, detail, visual consistency, or emotional depth correctly. The study concludes that AI still can't fully copy the emotional and visual depth that human artists can create. The finding emphasizes the uniqueness of original artwork and is expected to provide significant insights for the creative industry, opening up space for ethical discussion and enhancing visual literacy among designers, academics, and the public.